Performance of Tehran`s selected Public and Private Hospitals in Attracting Medical Tourists From Foreign Customers` Points Of View - F Azadi; M R Maleki; M Azmal (Tehran University of Medical Sciences, 2013)
Abstract Background: Medical tourism industry as one of the tourism dimensions results in a sustainable development and dynamic economy in countries. This study was conducted to examine performance of Tehran's selected public and private hospitals in attracting medical tourists from foreign costumers' points of view. Materials & Methods: This cross - sectional study was conducted in Tehran's selected public and private hospitals in 2011. The study population included 79 foreign patients who referred to four hospitals in Tehran as medical tourists. Data were collected using a self-made questionnaire which consisted of 23 questions which evaluated eight hospital performance components in attracting medical tourists. Descriptive and analytic statistics was used for data analysis. Results: Overall, the hospitals` performances were evaluated to be in an appropriate level. Through Patients` viewpoint, three components including staff number, staff performance quality and staff`s up to date knowledge and skills were in a proper level. Moreover, Staff's acquaintance with foreign languages and giving proper notifications were reported to be in a very poor level. There was a significant relationship between all of the performance components in attracting medical tourists and hospital ownership excluding staff's acquaintance with foreign languages and their familiarity with the facilities. Conclusion: Teaching international languages to key staffs and empowering their communication skills can be effective in attracting medical tourists. Considering this, both public and private hospitals must have a serious plan to achieve this goal.